Social Ties in Academia: A Friend is a Treasure - Tommaso Colussi (Institute for the Study of Labor (IZA), 2015)
This paper employs a unique dataset on articles, authors and editors of the top general interest journals in economics to investigate the role of social connections in the publication process. Ties between editors and authors are identified based on their academic histories. Results show that an editor's former PhD students and faculty colleagues experience an increase in their publication outcomes when this editor is in charge of a journal. The analysis of articles' citations suggests that connections ultimately improve the quality of published papers.
Keywords: A1; I23; J24; 330; academia; networks; human capital